2019
DOI: 10.1111/apt.15416
|View full text |Cite|
|
Sign up to set email alerts
|

Review article: can bugs be drugs? The potential of probiotics and prebiotics as treatment for non‐alcoholic fatty liver disease

Abstract: Summary Background Non‐alcoholic fatty liver disease (NAFLD) has become the most common chronic liver condition. A major current research effort is ongoing to find potential strategies to treat NAFLD‐non‐alcoholic steatohepatitis (NASH), with special attention to the gut microbiota. Multiple animal studies and pilot clinical trials are assessing different gut microbiota modulating strategies such as faecal microbiota transplantation, antibiotics, probiotics, prebiotics and synbiotics. Aim To review the role of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 104 publications
(255 reference statements)
0
27
0
1
Order By: Relevance
“…To determine the mechanisms of the anti-steatosis and anti-fibrotic changes in the liver after visceral nerve blockade, we examined changes in tight junctions of the small intestine, intestinal bacterial flora and SCFAs, which are reportedly related to NAFLD and NASH development (Koopman et al, 2019;Rahman et al, 2016).…”
Section: Effect Of Autonomic Nerve Signal On Hepatic Fibrosis In Cdaamentioning
confidence: 99%
See 1 more Smart Citation
“…To determine the mechanisms of the anti-steatosis and anti-fibrotic changes in the liver after visceral nerve blockade, we examined changes in tight junctions of the small intestine, intestinal bacterial flora and SCFAs, which are reportedly related to NAFLD and NASH development (Koopman et al, 2019;Rahman et al, 2016).…”
Section: Effect Of Autonomic Nerve Signal On Hepatic Fibrosis In Cdaamentioning
confidence: 99%
“…The etiology of the disease includes not only obesity and dyslipidemia but also impaired glucose tolerance, hypertension, insulin resistance, abnormal hormone secretion, genetic factors and gut-liver axis (Wiest et al, 2017;Tilg et al, 2020), and these factors have a complicated relationship (Drescher et al, 2019). The effect of the gut-liver axis has been focused on microbiota changes (Boursier et al, 2016;Hu et al, 2020), short-chain fatty acids (SCFAs) (De Vadder et al, 2014;Koopman et al, 2019) and tight junction (Miele et al, 2009;Gupta et al, 2020;Rahman et al, 2016), which are reportedly related to steatohepatitis, hepatic fibrosis (Loomba et al, 2017) and carcinogenesis (Yoshimoto et al, 2013) in NAFLD. However, as these factors are diverse and the pathologic network connecting these factors has not been elucidated, standard treatment methods for NAFLD have not been established.…”
Section: Introductionmentioning
confidence: 99%
“…However, changes in gut microbiota were not entirely consistent among studies (Kolodziejczyk et al, 2019). For example, among NAFLD individuals, an increase in Proteobacteria and Bacteroidetes has been reported (Boursier et al, 2016;Shen et al, 2017), while a reduction in Proteobacteria and Bacteroidetes was also observed (Shin et al, 2017;Koopman et al, 2019). Different ethnicities and living environments may help explain these discrepancies.…”
Section: Discussionmentioning
confidence: 96%
“…SCFAs improve hepatic autophagy and gut barrier function, and reduce the permeability of bacterial toxins. These gut products can reduce pro-inflammatory pathways and insulin resistance, which are associated with the progression of chronic liver disease [78,79] . The gut microbiota composition is dynamic and may be influenced by diet, hygiene and the use of antibiotics [80] .…”
Section: Gut Microbiotamentioning
confidence: 99%